Ответы и объяснения

  • kefa
  • главный мозг
2013-03-17T10:32:20+00:00

-4(х-3)+2(5-х)=4

-4х+12+10-2х=4

-6х+22=4

-6х=-18

х=3

ответ: 3

 

2-(у-0,6)-0,3(-2у-0,8)=5

2-у+1,2+0,6у+0,24=5

-0,4у+3,44=5

-0.4у=1,56

у=-3,9

Ответ: -3,9

 

Лучший Ответ!
  • Lemrhk
  • светило науки
2013-03-17T10:50:02+00:00

-4(х-3)+2(5-х)=4

-4х+12+10-2х=4

-6х+22=4

-6х=-18

 x=-18/-6

 х=3

Ответ: 3

***********************************

2-(у-0,6)-0,3(-2у-0,8)=5

2-у+1,2+0,6у+0,24=5

-0,4у+3,44=5

-0.4у=1,56

y=1,56/-0,4

у=-3,9

Ответ: -3,9